Android app development for contact tracing scheme - Chan, Jansen Lawrence (Nanyang Technological University, 2021)
The COVID-19 pandemic has affected virtually everyone around the globe, forcing local authorities to implement various measures that can help to contain the virus. Technology has played a significant factor in mitigating the spread of COVID-19. In Singapore, SafeEntry and TraceTogether were two of the ways that the government has utilised technology, to enhance contact tracing efforts in the country. In this project, an Android mobile application that aims to further improve current contact tracing schemes was developed. By utilising Bluetooth Low Energy (BLE) technology, the app will provide an alternative way of receiving the information needed to check in and out of SafeEntry, which is currently not being used in Singapore at the time of writing. The report will focus on the application development process and the resulting application interface and functions achieved. It will also discuss some of the problems and limitations that were faced, before concluding with suggestions for future work.